IMPROVING STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXT THROUGH ONE STRAY TECHNIQUE - Andayani, Erda Dwi; Sudarsono, Sudarsono; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe result of the research showed that students could comprehend narrative text with good comprehension. The problem of the research  was  students got difficulty to find out the meaning of the words, got less information during learning process because they were not active in reading the narrative text and its generic structure. Reading narrative text helped the students in finding the information about the story. The teacher explained the generic structure of narrative text to studying. The student sharing the information in the second group helped them in comprehending a narrative text. This research found out that there was an improvement of students reading comprehension in narrative text  for each cycle by Implementing One Stray Technique in teaching reading comprehension and students’ score improvements was better.Keywords: Reading Comprehension, Narrative Text, One Stray Strategy.